Assessment of Bioenergy Potential of Lemon Grass - A. M. Rabe; B. L. Aleiro; A. Galadima; S. Baqi; H. M. Maikudi (Archives of Current Research International, 2019)
Grasses can serve as an alternative biomass for the production of bioenergy which plays a vital role in solving some of the challenges faced in the production of renewable energy and also help in tackling some of the environmental challenges faced all over the world. In this research, the phytochemical and biofuel content of Cymbopogon citratus was assessed. The phytochemical screening and proximate analysis were carried out according to standard qualitative and quantitative methods. Alkaloids, balsam, flavonoids, glycosides, saponin, carbohydrates, protein, volatile oil, minerals are analyzed. Bioenergy was produced using enzymatic hydrolysis after pretreatment under different pH viz: pH 5, pH 7 and pH 8 all under an ambient temperature of 36˚C. Each of the pretreated samples of varying pH was then fermented using Saccharomyces cerevisiae. Each of the pre-treatment under three different pH was made in triplicate. The absorbance was determined for reducing sugar and at the end of the production, the pretreated samples were subjected to Gas chromatography and mass spectroscopy to analyze the end product of bioenergy produced. The result for phytochemicals shows the presence of flavonoids and alkaloids (1.60%) followed by volatile oil (7%), saponin (3.20%) and tannins (0.6%). The result for proximate analysis shows that lemon grass has the highest percentage of carbohydrates (87.63%). This was followed by ash (11.67%), protein (11.14%) and fibres (2.83%). However, the mineral analysis shows the presence of Calcium (1.88 mg/ml), Magnesium (0.13 mg/ml), Phosphorous (5.87 mg/ml), Potassium (2866.67 mg/ml) and Sodium (89.17 mg/ml). The absorbance in C. citratus is higher at pH 5 (0.0651). The GC-MS analysis of the bioenergy produced shows the presence of Ethyl alcohol (bioethanol) in all the samples at different pH. Hydrazine carboxamide was present in all the treatments under different pH. In addition glycidol, acetyldehyde, acetic acid, 1,2-propanediamine were found present, having fuel potential and are good source of gasoline. These are produced as a result of fermentation and enzymatic activities of the organic compound present in the biomass sample used.